Revisiting the law and governance of trafficking, forced labor and modern slavery - Kotiswaran, Prabha (Cambridge studies in law and society, 2017)
"Trafficking typically involves the movement of persons for exploitation for a third party's benefit. Inspired by the Palermo protocols, several states today criminalize trafficking, and it is perceived as an issue of serious organized crime. This edited volume brings together academics, activists and officials from international organizations who believe that the choice of a criminal law response arose from a particular alignment of geo-political interests of developed countries in the wake of globalization. Adopting an inter-disciplinary, multi-stakeholder approach, contributors to this volume instead understand trafficking through the lens of labor migration and extreme exploitation and consequently rethink both the law and governance of trafficking. This volume considers many key factors, including the evolving international law on trafficking, the relationship between trafficking and domestic migration law and policy, as well as newly emergent techniques of governance including indicators, with a view to exploring prospects for economic justice in a globalized world"--